Ursodeoxycholic acid in cholestasis: linking action mechanisms to therapeutic applications - Roma, Marcelo Gabriel (2011)
UDCA (ursodeoxycholic acid) is the therapeutic agent most widely used for the treatment of cholestatic hepatopathies. Its use has expanded to other kinds of hepatic diseases, and even to extrahepatic ones. Such versatility is the result of its multiple mechanisms of action. UDCA stabilizes plasma membranes against cytolysis by tensioactive bile acids accumulated in cholestasis. UDCA also halts apoptosis by preventing the formation of mitochondrial pores, membrane recruitment of death receptors and endoplasmic-reticulum stress. In addition, UDCA induces changes in the expression of metabolizing enzymes and transporters that reduce bile acid cytotoxicity and improve renal excretion. Its capability to positively modulate ductular bile flow helps to preserve the integrity of bile ducts. UDCA also prevents the endocytic internalization of canalicular transporters, a common feature in cholestasis. Finally, UDCA has immunomodulatory properties that limit the exacerbated immunological response occurring in autoimmune cholestatic diseases by counteracting the overexpression of MHC antigens and perhaps by limiting the production of cytokines by immunocompetent cells. Owing to this multi-functionality, it is difficult to envisage a substitute for UDCA that combines as many hepatoprotective effects with such efficacy. We predict a long-lasting use of UDCA as the therapeutic agent of choice in cholestasis.